Knowledge, Attitude and Practices of Dental Erosion related to Acidic Dietary Intake among Medical Undergraduates. - Saman Hakeem, Anum Baqar, Farnaz Ilyas, Abid Mohsin, Kiran F. M. Bana, M. Faisal Fahim, S. A. Abbas Zaidi, W. Baksh Kadri (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: To assess knowledge, attitude and practice of dental erosion related to dietary acidic intake among medical undergraduates. Methods: It was a cross sectional study conducted at Bahria University Medical and Dental College, Karachi from March-2019 to November 2019. The validated questionnaire was used to assess the study objectives. There were five sections in the study tool including demographic data, knowledge, self-reported signs and symptoms, attitude and practices of acidic dietary intake. The data was entered on SPSS version 23.0 for analysis. P-value <0.05 was considered as statistically significant. Results: From total of 500 subjects; 498 questionnaires were completed in all aspects; hence the response rate was 99.6%. Respondents comprised of both males and females having age range from 17 to 25 years with a mean age of 20.82+SD 1.76. Majority of participants (74.4%) had high level of knowledge regarding dental erosion. Statistically significant association was found (p-value=0.02) when compared to level of knowledge with attitude. While assessing the association between practice and self-reported sign/symptoms; significant association was found in regards to frequency and timing of acidic dietary intake at a p-value of 0.000. Conclusion: Majority of participants had high level of knowledge regarding erosion as related to acidic dietary intake and was positively reflected in their attitude. Overall, natural fruit juices were the highest consumed drinks followed by carbonated drinks. Keywords: Dental erosion, Dietary behavior, Medical Undergraduates, Carbonated drinks, Dietary habits.